The Political Incorporation of Undocumented Youth. (30th May 2018) - Wong, Tom K; García, Angela S; Valdivia, Carolina
Abstract: This article develops and empirically tests a model of political incorporation for undocumented youth in the United States, focusing on nonvoting forms of political engagement. Using one of the ﬁrst nationwide surveys of undocumented millennials between the ages of 18 and 35 ( n = 1, 472), we show that (1) undocumented youth express much higher levels of political efficacy and participation than the literature on immigrant political incorporation leads us to expect, (2) membership in organizations that work on immigration-related issues is a main determinant of this sense of political efficacy, and (3) through mediation analysis, that organizational membership (the mediator) inﬂuences how political efficacy affects political participation, and not the other way around. The literature on immigrant political incorporation is vast, but precedent studies too often focus on formal acts of political participation, such as naturalization and voting, by those with lawful immigration status. With an analytical focus on youth without lawful immigration status, this article contributes to theoretical and empirical knowledge about how and to what extent undocumented youth become politically active and engaged despite the many obstacles that exist to their formal participation in politics.